Classification of potential habitat of the Central American tapir (Tapirus bairdii Gill, 1865) for their conservation in Guatemala - García Vettorazzi, Manolo José; Leonardo Manrique, Raquel (THERYA, 2016)
Tapir distribution in Guatemala has dropped dramatically over the past century, causing populations to be restricted to protected areas of the northeastern region of the country. This study seeks to determine the conservation status of the species habitat in the country based on its presence, the importance of forest remnants in system connectivity and coverage of formal mechanisms of protection. The Maxent distribution modeling was performed using 62 records of presence 10 climatic variables and terrain elevation. The resulting map was reclassified into a binary map (cutoff 0.3) and using the Morphological Spatial Pattern Analysis tool of GUIDOS program, a map in which the 12 larger forest remnants were selected was obtained. To these remnants the Integral Connectivity Index (dIIC) with Sensinode CONEFOR program was calculated. From the above, classifications of forest remnants were established to determine the conservation status of the species habitat. The potential distribution model had an area under the curve (AUC) of 0.815 and from the binary map it was estimated that the potential habitat of the tapir in 2012 was 26,095.82 km2. The Morphological Spatial Pattern Analysis showed that the tapir habitat is mainly composed of core area (43 %). The connectivity analysis indicated that the forest remnants of the Maya Biosphere Reserve (Northwest and East) and the Sierra de las Minas Biosphere Reserve have a dIIC of 33.505662, 0.51311405 and 0.38876015, respectively. The remnants of larger extension and higher dIIC correspond to the northeast and west section of the Maya Biosphere Reserve and Sierra de las Minas Biosphere Reserve. Compared with previous studies, there is a tendency in reducing coverage and degradation (fragmentation) tapir habitat, highlighting the vulnerability of the species populations in the country.